Does Allograft Augmentation of Small-Diameter Hamstring Autograft ACL Grafts Reduce the Incidence of Graft Retear?. (February 2017) - Pennock, Andrew T.; Ho, Brian; Parvanta, Kristina; Edmonds, Eric W.; Chambers, Henry G.; Roocroft, Joanna H.; Bastrom, Tracey P.
Background: Small-diameter hamstring tendons are frequently encountered during anterior cruciate ligament (ACL) reconstructions in patients with short stature or those who are skeletally immature. The role of augmenting these small-diameter autografts with allograft is unclear. Purpose: To assess clinical outcomes and failure rates in adolescent patients with small hamstring tendon autografts (<7 mm) that were either augmented with soft tissue allograft or accepted "as is" and not augmented. Study Design: Cohort study; Level of evidence, 3. Methods: A retrospective chart review of all primary ACL reconstructions performed with hamstring autografts identified 385 patients, of whom 50 (13%) had a quadrupled (semitendinosus-gracilis) graft size less than 7 mm. Patients were grouped based on the surgeon's preference either to augment these grafts with allograft (augmented group; n = 26) or to accept the smaller autograft (nonaugmented group; n = 24). Preoperative demographic, injury, and intraoperative data were documented. All patients were contacted to obtain information about outcome scores, subsequent procedures, and complications. Forty patients (20 in each group) were available for 2-year follow-up. Results: The mean age of the entire cohort was 15.7 years (range, 12-18 years), and 38% were male. No between-group differences were found with respect to any of the preoperative or intraoperative variables except extremity side. The mean graft size for the augmented group was 8.9 mm and for the nonaugmented group was 6.4 mm. At a mean follow-up of 3 years, 6 (30%) of the patients in the augmented group had a graft failure, whereas only 1 (5%) in the nonaugmented group had a failure ( P = .04). Five of the 6 augmented failures occurred within 1 year of surgery, whereas the single failure in the nonaugmented group occurred 2.7years postoperatively. No differences were noted in the reported outcomes between patients in the augmented and nonaugmented groups who did not experience graft failure (Lysholm score, 88 vs 92; Tegner score, 6.4 vs 6.3; single-assessment numeric evaluation score, 86 vs 86; satisfaction, 8.4 vs 8.9, respectively). Conclusion: Adolescents undergoing an ACL reconstruction frequently have small hamstring tendon autograft size. The augmentation of these small grafts with allograft does not reduce graft failure rates and may in fact lead to higher retear rates, with earlier graft failure.